2008
DOI: 10.1186/1472-6963-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Developing the content of two behavioural interventions: Using theory-based interventions to promote GP management of upper respiratory tract infection without prescribing antibiotics #1

Abstract: Background: Evidence shows that antibiotics have limited effectiveness in the management of upper respiratory tract infection (URTI) yet GPs continue to prescribe antibiotics. Implementation research does not currently provide a strong evidence base to guide the choice of interventions to promote the uptake of such evidence-based practice by health professionals. While systematic reviews demonstrate that interventions to change clinical practice can be effective, heterogeneity between studies hinders generalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 27 publications
1
65
0
1
Order By: Relevance
“…Although the study was powered on behavioural intention as the primary outcome (because intention features in both theories on which the intervention was based), the data The study had three strengths: it replicates previous work, it used a randomised design and it had a theoretical rationale for selecting intervention components. The work described here, together with that in a sister paper [12] (where we found that the web-based IME identified 8/10 of the predictors of prescribing behaviour identified in the paper-based IME), have largely reproduced results obtained in an earlier, paper-based IME [10,11], which reassures us that the IME methodology is robust. The randomised design is the best way of running an experiment to test the effectiveness of proposed interventions.…”
Section: Of 21supporting
confidence: 81%
See 3 more Smart Citations
“…Although the study was powered on behavioural intention as the primary outcome (because intention features in both theories on which the intervention was based), the data The study had three strengths: it replicates previous work, it used a randomised design and it had a theoretical rationale for selecting intervention components. The work described here, together with that in a sister paper [12] (where we found that the web-based IME identified 8/10 of the predictors of prescribing behaviour identified in the paper-based IME), have largely reproduced results obtained in an earlier, paper-based IME [10,11], which reassures us that the IME methodology is robust. The randomised design is the best way of running an experiment to test the effectiveness of proposed interventions.…”
Section: Of 21supporting
confidence: 81%
“…The work described here is part of a study to evaluate the IME methodology itself by replicating an earlier, paper-based IME [10,11] and describes a randomised evaluation of two interventions -a persuasive communication used in the paperbased IME and an action plan developed from the predictors described in our earlier publication [12] -against a 'no intervention' comparator. To be reassured, (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, an intervention modeling process has been developed that uses setting-specific behavioral theories for selecting interventions. 59 In future studies, such an approach may improve the likelihood of successful interventions. Detailed studies directed at understanding the differences among endoscopists and endoscopy environments, which include nurses, endoscopy volume, and other factors, may be helpful in identifying and developing performance-related interventions for improving adenoma detection rates.…”
Section: Discussionmentioning
confidence: 98%